Authentication of area fingerprint scanners. (October 2019) - Ivanov, Vladimir I.; Baras, John S.
Highlights: Area fingerprint scanners can be distinguished based on their scanner pattern. The pattern is their sufficiently unique, persistent, and unalterable characteristic. We propose a simple method to extract the pattern and compare it with another one. Tests on 22 scanners of the same model yielded estimated EERs in the order of 1e-7. The pattern enhances biometric security by authenticating the fingerprint scanner. The pattern can be used as an authenticator whereas the biometrics is an identifier. Other applications include contextual authentication and source of randomness. Abstract: Each area fingerprint scanner (sensor) has a unique scanner pattern that can be used to distinguish one scanner from another. The pattern results from imperfections in the conversion of the signal acquired from the object, applied to the scanner, into a digital image. The scanner pattern is a sufficiently unique, persistent, and unalterable intrinsic characteristic of the fingerprint scanners even to those of the same technology, manufacturer, and model. We propose a model of the image acquisition in widely-used capacitive area fingerprint scanners and a method to extract the pattern from a single image and compare it with a similarly extracted pattern from another image. The method is very simple and computationally efficient yet extremely accurate, achieving an equal error rate in the order of 1e-7 for 22 scanners of exactly the same model, and is also robust in a wide range of conditions. The scanner pattern can be used to enhance the security of a biometric system by detecting an attack in which an image containing the fingerprint pattern of the legitimate user and acquired by the authentic fingerprint scanner has been replaced by another image that may still contain the fingerprint pattern of the legitimate user but has been acquired by another, unauthentic fingerprint scanner, i.e., for scanner authentication .